Challenges encountered in providing integrated HIV, antenatal and postnatal care services: a case study of Katakwi and Mubende districts in Uganda - Ahumuza, Sharon E.; Rujumba, Joseph; Nkoyooyo, Abdallah; Byaruhanga, Raymond; Wanyenze, Rhoda K. (Reproductive health, 2016)
Integration of sexual and reproductive health (SRH), HIV/AIDS and maternal health (MH) services is a critical strategy to confront the HIV/AIDS epidemic, high maternal mortality and the unmet need for contraception. In 2011 the AIDS Information Centre (AIC) in partnership with the Ministry of Health implemented SRH, HIV/AIDS and MH integration services in the districts of Katakwi and Mubende in Uganda. This paper documents challenges encountered in providing these integrated services in the two districts. This was a cross-sectional qualitative study conducted in Mubende and Katakwi districts in Uganda. Data were collected using 10 focus group discussions with 89 women attending ANC and postnatal care and 21 key informant interviews with district managers and health workers who were involved in the integrated service delivery. Content thematic approach was used for data analysis: The study findings indicate that various challenges were encountered in integrating HIV, ANC and PNC services. Major challenges included inadequate staff, gaps in knowledge of service providers especially with regard to provision of long-term family planning, limited space, shortage of critical supplies such as HIV test kits, drugs and gloves.
Keywords: Integrated HIV; Antenatal services; Postnatal service and challenges in providing integrated services